2010
DOI: 10.1016/j.ccr.2009.12.041
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Are Activated in Incipient Neoplasia to Orchestrate Tumor-Promoting Inflammation in an NF-κB-Dependent Manner

Abstract: Cancer-associated fibroblasts (CAFs) support tumorigenesis by stimulating angiogenesis, cancer cell proliferation, and invasion. We demonstrate that CAFs also mediate tumor-enhancing inflammation. Using a mouse model of squamous skin carcinogenesis, we found a proinflammatory gene signature in CAFs isolated from dysplastic skin. This signature was maintained in CAFs from subsequent skin carcinomas and was evident in mammary and pancreatic tumors in mice and in cognate human cancers. The inflammatory signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,132
5
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,317 publications
(1,211 citation statements)
references
References 81 publications
40
1,132
5
15
Order By: Relevance
“…In agreement with this finding, Mueller et al 41 recently reported that stromal fibroblasts could generate an inflammatory microenvironment to promote colorectal liver metastases. In addition, recently Erez et al 42 demonstrated that cancerassociated fibroblasts mediate tumor-enhancing inflammation in a nuclear factor-B-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this finding, Mueller et al 41 recently reported that stromal fibroblasts could generate an inflammatory microenvironment to promote colorectal liver metastases. In addition, recently Erez et al 42 demonstrated that cancerassociated fibroblasts mediate tumor-enhancing inflammation in a nuclear factor-B-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs in skin, breast, and pancreatic cancers were found to express a pro-inflammatory gene signature including cyclooxygenase (COX)-2, osteopontin (OPN), CXCL1, CXCL2, IL-6, and IL-1β. In addition, dermal CAFs isolated from a transgenic mouse model of squamous cell carcinogenesis contribute to macrophage recruitment, angiogenesis, and enhanced tumour growth in a nuclear factor-kappa B (NF-κB)-dependent manner [39]. A similar pro-inflammatory gene signature was identified in a subtype of CAFs in inflammation-induced gastric cancer [40].…”
Section: From Tumour Suppressors To Tumour Promotersmentioning
confidence: 99%
“…IL-1β was expressed by resident immune cells in hyperplastic skin and activated a pro-inflammatory gene signature in dermal CAFs; however, this signature was not induced in CAFs derived from either B-cell-deficient or FcRγ-deficient mice, thus indicating that CAF activation is downstream of humoral immune-mediated activation of inflammatory leukocytes in neoplastic tissue [55]. Thus, B cells produce antibodies that are deposited in neoplastic skin by leaky angiogenic vasculature; these in turn engage FcγR on resident immune cells and induce secretion of IL-1, which activates proinflammatory properties of CAFs [39,54,56].…”
Section: Activation By Paracrine Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…While often referred to generically as CAFs, there are evidently a number of distinctive fibroblastic cell types encompassed by this designation, including recruited myofibroblasts expressing smooth muscle actin, and activated (‘reactive’) resident tissue fibroblasts (Pietras and Ostman, 2010). The functionality of CAFs has been demonstrated for example by co‐injection of CAFs together with tumor cells, which enhances tumor growth by promoting ECM synthesis and stiffening, inducing angiogenesis, and recruiting growth‐promoting inflammatory cells such as macrophages (Erez et al., 2010; Kalluri and Zeisberg, 2006; Orimo et al., 2005; Tlsty and Coussens, 2006). CAFs are particularly abundant in certain human cancers, such as PDAC, and in various carcinomas at advanced stages of progression (e.g., breast and colorectal cancer).…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%